The Effect of Group Guidance Services Using Role Playing Techniques on the In-terpersonal Communication Skills of Grade VII Students at MTs Nurus Salam Deli Tua - Yofita Intan Putri Kasih; Dina Hidayati; Nur Asyah; Nurul Azmi (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2025)
This study aims to determine the effect of group guidance services with role-playing techniques on the interpersonal communication skills of seventh-grade students at MTs Nurus Salam Deli Tua. Interpersonal communication skills are crucial for adolescents to interact effectively with their social environment. This study employs a quantitative approach with a quasi-experimental method in the form of a one-group pretest-posttest design. The population of this study consisted of 65 students, with a sample of 10 students selected purposively based on the results of initial observations. The instrument used was an interpersonal communication questionnaire that had been tested for validity and reliability. Data analysis was performed using a t-test. The results showed a significance value of 0.000 < 0.05, indicating a significant effect of group guidance services with role-playing techniques on students' interpersonal communication skills.